Magnesium Requirements in Children: Recommendations for Reevaluation and Comparison With Current Evidence for Adults. Issue 5 (September 2019) - Cao, Sisi; Hodges, Joanna K.; McCabe, Linda D.; Weaver, Connie M.
Abstract : Magnesium (Mg), a cofactor in 300 enzymes, is essential for energy transfer and adequate vitamin D status and plays an important structural role with 60% of bodily reserves residing in bone. The Food and Nutrition Board recommendations for dietary intake of Mg, the Dietary Reference Intakes, have not been updated since 1997. Current recommendations for children were set based on an intake producing positive Mg balance. Population-based studies showed that the average intakes in children are suboptimal relative to the current recommendation. Newer evidence suggests Mg requirement should be related to body size. Other potential modifying factors of Mg requirements include calcium and sodium intake and chronic disease state. Future research is needed to refine public health recommendations for Mg and to establish the new Dietary Reference Intakes category of Chronic Disease Risk Reduction level for Mg, especially for children.